Can public transit subsidies be warranted for improving air quality and health outcomes?: evidence from the São Paulo metropolitan area for a second-best policy - Maeji, Daniela Stucchi da Silva (2018)
This research investigates the impacts of public transit on air pollution and health in the Sao Paulo Metropolitan Area. Subsidies for public transport systems are highly controversial and there is no consensus in the literature on their efficiency. One of the reasons advanced to support public transit subsidization refers to the negative externalities that automobile use generates, such as air pollution and its adverse health effects, assuming that these external costs are not fully internalized by automobile users through other policies. However, the empirical question remains as to whether increasing transit provision is welfare-enhancing in this respect, especially in megacities of developing countries. To be able to infer a causal relationship, we adopted a quasi-experimental approach using public transit strikes to identify exogenous variations in the outcomes of interest. The results suggest significant benefits for providing public transit, especially with regard to impacts on traffic-related air pollutants and respiratory illness in young children, with stronger effects for those residing near more congested arterial roads. It is expected that the findings will inform policy makers’ efforts to evaluate existing fare subsidies and potential pricing reforms, especially in times of fiscal stress.